The influence of the polyamine synthesis pathways on Pseudomonas syringae virulence and plant interaction - Solmi, Leandro (2025)
This study investigates the role of polyamine biosynthesis in the pathogenesis of the bacterial phytopathogen Pseudomonas syringae pv. tomato. Through a comprehensive phenotypic analysis of mutant strains affected in the synthesis of putrescine and spermidine, we reveal a complex interplay between this metabolic pathway and bacterial virulence. Disruption of putrescine synthesis impairs a variety of virulence traits such as motility, biofilm formation, siderophore production, prevention of plant stomatal closure and the functionality of the type III secretion system. This is reversed by reintroducing the deleted genes, but not by the supplementation of culture media with putrescine or apoplastic washing fluids (AWF). Similarly, suppression of spermidine biosynthesis results in a comparable phenotype. However, in this case, the wild-type phenotype is restored by adding spermidine, AWF or expressing the spermidine synthase gene. We conclude that both putrescine and spermidine are important for bacterial virulence and that plant-derived spermidine can partially compensate for bacterial needs. Accordingly, whereas putrescine deficiency leads to a hypovirulent phenotype, spermidine synthesis perturbation does not affect plant colonization. These findings emphasize the critical role of polyamine metabolism in the plant invasion process by bacterial pathogens.